2016
DOI: 10.1186/s12906-016-1333-4
|View full text |Cite
|
Sign up to set email alerts
|

Vinegar amount in the process affected the components of vinegar-baked Radix Bupleuri and its hepatoprotective effect

Abstract: BackgroundBupleuri Radix (in Chinese Chaihu), the dried roots of Bupleurum Chinense DC, is a traditional Chinese medicine widely used to treat fever, hepatitis, jaundice, nephritis, dizziness. When baked with vinegar, its effect is more focused on liver related disease. This paper was undertaken to determine the best vinegar amount in the processing and explore its key efficacy components.MethodsHepatoprotective effects of Radix Bupleuri after processing with different amount of vinegar (1:5, 2:5, 3:5) were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Triterpene saponins are common and the main effective components in BR and liquorice, and triterpene saponins have received increasing attention in recent years because of their variety and extensive biological activity. Pharmacological studies have revealed that saponins from BR have anti‐inflammatory, immunoregulation, and anti‐hepatic fibrosis effects . In addition, a wide array of biological activities has been ascribed to saponins from liquorice, including anti‐inflammatory, antiarrhythmia and hepatoprotective effects, among others .…”
Section: Introductionmentioning
confidence: 99%
“…Triterpene saponins are common and the main effective components in BR and liquorice, and triterpene saponins have received increasing attention in recent years because of their variety and extensive biological activity. Pharmacological studies have revealed that saponins from BR have anti‐inflammatory, immunoregulation, and anti‐hepatic fibrosis effects . In addition, a wide array of biological activities has been ascribed to saponins from liquorice, including anti‐inflammatory, antiarrhythmia and hepatoprotective effects, among others .…”
Section: Introductionmentioning
confidence: 99%
“…Zhao, Wang, et al. (2016); Zhao, We, et al. (2016) demonstrated that the transfer ratios (TRs) of the investigated elements were different and that it might depend on the types of elements, the plant species, and the extraction methods.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that Co and As had the highest TRs values, thus the two elements should be closely monitored to prevent further transferring from herbal medicines to decoctions. In terms of the TRs research on heavy metals, water extraction can significantly reduce the contents (Zhao, Wang, et al., 2016; Zhao, We, et al., 2016). The result also points out that the PaoZhi method may help heavy metals in the herb dissolve more easily into its decoction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations